Genetic Predictors of Depressive Symptoms in the Look AHEAD Trial. Issue 9 (November 2015) - McCaffery, Jeanne M.; Papandonatos, George D.; Faulconbridge, Lucy F.; Erar, Bahar; Peter, Inga; Wagenknecht, Lynne E.; Pajewski, Nicholas M.; Anderson, Andrea; Wadden, Thomas A.; Wing, Rena R.
ABSTRACT: Objectives: Numerous studies have found elevated depressive symptoms among individuals with Type 2 diabetes, yet the mechanisms remain unclear. We examined whether genetic loci previously associated with depressive symptoms predict depressive symptoms among overweight/obese individuals with Type 2 diabetes or change in depressive symptoms during behavioral weight loss. Methods: The Illumina CARe iSelect (IBC) chip and Cardiometabochip were characterized in 2118 overweight or obese participants with Type 2 diabetes from Look AHEAD (Action for Health in Diabetes), a randomized trial to determine the effects of intensive life-style intervention and diabetes support and education on cardiovascular morbidity and mortality. Primary analyses focused on baseline Beck Depression Inventory (BDI) scores and depressive symptom change at 1 year. Results: Of eight single nucleotide polymorphisms (SNPs) in six loci, three a priori SNPs in two loci (chromosome 5: rs60271; LBR : rs2230419, rs1011319) were associated with baseline BDI scores, but in the opposite direction of prior research. In joint analysis of 90, 003 IBC and Cardiometabochip SNPs, rs1543654 in the region of KCNE1 predicted change in BDI scores at Year 1 in diabetes support and education ( β = −1.05, standard error [SE] = 0.21, p = 6.9 × 10 −7 ) at the level of chip-wide significance, while also showing a nominal association with baseline BDI ( β = 0.35, SE = 0.16, p = .026). Adjustment for antidepressant medication and/or limiting analyses to non-Hispanic white individuals did not meaningfully alter results. Conclusions: Previously reported genetic associations with depressive symptoms did not replicate in this cohort of overweight/obese individuals with Type 2 diabetes. We identified KCNE1 as a potential novel locus associated with depressive symptoms. Abstract : Supplemental digital content is available in the text.